Study of CuSbSe2 thin films grown by pulsed laser deposition from bulk source material. (January 2021) - Goyal, Deepak; Goyal, C.P.; Ikeda, H.; Gopalakrishnan, C.; Malar, P.
Abstract: In this paper, we discuss the details of growth of CuSbSe2 chalcostibite thin films via pulsed laser deposition using bulk ball milled compound. Thin film growth conditions, in particular pulsed laser energy was optimized to obtain the near stoichiometric thin films. Films were grown at room temperature as well as at 400  ° C and as grown films were post annealed at 400  ° C to see annealed induced effects. Material characteristics of the thin films were evaluated in detail using X-ray diffraction, X-ray photoelectron spectroscopy, UV–Vis–NIR spectroscopy and Raman spectroscopy studies. Scanning electron microscopy and dynamic force microscope measurements revealed the morphology as well as smoothness of the thin films. Hall coefficient values measured positive and carrier concentration value of 1.2 × 10 18 cm −3 for the films grown at 400  ° C. Absorption coefficient values of the order of ~10 5  cm −1 in the entire visible region and band gap of ~1.2 eV observed infer favorable photovoltaic characteristics.